What constitutes expertise in research ethics and integrity?. (January 2020) - Braun, Robert; Ravn, Tine; Frankus, Elisabeth
In this paper we reflect on the looming question of what constitutes expertise in ethics. Based on an empirical program that involved qualitative and quantitative as well as participatory research elements we show that expertise in research ethics and integrity is based on experience in the assessment processes. We then connect traditional concepts of expertise as "improved performance" with deliberate practice activities and, based on our research findings, show that ethical assessment experience is a form of deliberate practice. This in our view has further ramifications in the design and recruitment processes of ethical assessment units performing research ethics and integrity assessment.